2017
DOI: 10.1016/j.jvs.2017.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Administration of Adult Human Bone Marrow-Derived, Cultured, Pooled, Allogeneic Mesenchymal Stromal Cells in Critical Limb Ischemia Due to Buerger's Disease: Phase II Study Report Suggests Clinical Efficacy

Abstract: limb threatening ischemia. The thought that appropriate blood pressure control is detrimental to patients with claudication due to vascular occlusive disease is a myth. Even B-blockers do not appear to cause worsening of PAD symptoms in those requiring treatment as confirmed decades ago via a meta-analysis (Arch Intern Med 1991;151:1769-76). This article confirms the concept with a current analysis of pertinent studies and provides some data to suggest that in patients with intermittent claudication such treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…These cells are enriched for precursor cells that could be efficacious for therapy [194]. Stempeutics Research's specifications for their allogeneic BMMSC product, Stempeucel, includes parameters such as morphology (fibroblastic and spindle-shaped), cell counts of 180-220 million cells per bag, viability of >85%, ISCT-defined surface marker levels >80% along with CD166 > 80% [71] and CD133 < 5% as their release criteria for administration [195,196]. As more strategies evolve and new criteria are published, the selection panel is continuously being developed.…”
Section: Economic Potential and Market Impact Of Msc Research And Thementioning
confidence: 99%
“…These cells are enriched for precursor cells that could be efficacious for therapy [194]. Stempeutics Research's specifications for their allogeneic BMMSC product, Stempeucel, includes parameters such as morphology (fibroblastic and spindle-shaped), cell counts of 180-220 million cells per bag, viability of >85%, ISCT-defined surface marker levels >80% along with CD166 > 80% [71] and CD133 < 5% as their release criteria for administration [195,196]. As more strategies evolve and new criteria are published, the selection panel is continuously being developed.…”
Section: Economic Potential and Market Impact Of Msc Research And Thementioning
confidence: 99%
“…Another concept emerging from meta-analysis is that the response to CD34 + MNCs may be dose-dependent. In support to this hypothesis, treatment of NO-CLI with GCS-Fmobilized-or enriched CD34 + MNCs displayed encouraging results [51,57,58]. Regarding mechanisms, previous studies on CD34 + MNCs showed that they can improve limb reperfusion through extracellular vesicle (EV)-mediated delivery of angiogenic miRNAs [22, 48•, 59, 60•].…”
Section: Mononuclear Cellsmentioning
confidence: 79%
“…Recent clinical studies have demonstrated that the administration of MSCs to patients with CLI is safe (Das et al 2013;Gupta et al 2013Gupta et al , 2017Lasala et al 2011;Lu et al 2011). Given these results and a wealth of encouraging preclinical data, MSCs have become the most clinically relevant CT for testing in CLI patients.…”
Section: Discussionmentioning
confidence: 99%
“…Based on regulatory guidelines, it is recommended that preclinical toxicity and biodistribution assessments using the intended good manufacturing practices (GMP) grade CT product are carried out under good laboratory practices (GLP) prior to submitting an application for clinical testing (US FDA 2013;EMA 2008). It therefore was evident to us that despite the preclinical and clinical data demonstrating safety of human MSCs (hMSCs; Gupta et al 2017;Ramot et al 2009;Guess et al 2017;Creane et al 2017;Yun et al 2016;Schmuck et al 2016;Rengasamy et al 2016;Bura et al 2014;Braun et al 2016;Chen et al 2015;Wang et al 2012;Macisaac et al 2012) that preclinical toxicity and biodistribution studies would be required to assess the safety of our GMP CT product. It was also clear that the product should be administered in a similar manner to the proposed clinical route, which in our case was IM.…”
mentioning
confidence: 99%